Practice of Multidisciplinary Collaborative Chain Management Model in Constructing Nursing Path for Acute Trauma Treatment. (30th July 2022) - Xiang, Shuangqiong; Tang, Weiping; Shang, Xiaoyuan; Ni, Hongyan
Abstract : Prompt and effective treatment is the key to improve the prognosis of patients with acute trauma, and nursing plays an important role. However, conventional nursing has many limitations. Some studies have pointed out that the multidisciplinary collaborative chain management model can optimize the emergency procedures, ensure the continuity of the emergency treatment process, and optimize the treatment details. This study analyzed the practice of constructing an acute trauma care pathway based on a multidisciplinary collaborative chain management model. The results showed that the application of the multidisciplinary collaborative chain management model in the construction of acute trauma treatment nursing paths can enhance the emergency efficiency and nursing treatment, prevent the occurrence of adverse events, and improve the prognosis of patients.